ANALISIS SIFAT KONDUKTIVITAS LISTRIK PADA BEBERAPA JENIS MATERIAL DENGAN METODE POTENSIAL JATUH - Muh. Said L. Muh. Said L. (Teknosains, 2013)
The measurement of conductivity rock coat conducted by using potential method fall. Target of this research is to know how big assess electrics conductivity some homogeneous material type which obtained potential fall and know graph characteristic is nature of conductivity various same material type to function apart friction of potential electrode fall. The pursuant to result of the measurement, that every material have conductivity value which vary, where land containing of brine (salt) conductivity value equal to (0,4760-0,450)m-1, sand coat and gravel equal to (0,0096-0,0078)  m-1, limestone equal to (0,0151-0,01488)  m-1, clay land equal to (0,165-0,156)  m-1, and limestone contain chalk equal to (0,00269-0,00251)  m-1. Rock type/land owning larger ones conductivity is land containing of brine (salt) while smallest conductivity is limestone containing of chalk. Conductivity value every rock coat is land containing of brine (salt) = 0,4626  m-1 with DK=91,47%, sand coat and gravel = 0,0087  m-1 with DK=86,77%, limestone = 0,0150  m-1 with DK=92,18%, clay land = 0,1608  m-1 with DK=83,04%, and limestone containing of chalk = 0,00256  m-1 with DK=92,40%. From is fifth of material type anticipated that conductivity value vary to be caused by the existence of difference of amenity electrics current to emit a stream of in each passed by rock compiler material. Strong difference of current to emit a stream of in rock coat medium very is base on nature of passed by material physical. Nature of the physical for example is porosity, permeability, mass density, and item size measure distribution.